Problematika Pemanfaatan Program Pt. Pertamina Pada Masyarakat Desa Klayas - Sinta Nuria Gufron; Muh Rusdi Rasyid; Rabiudin Rabiudin (Prodi Ekonomi Syariah IAIN Sorong, 2022)
Corporate Social Responsibility (CSR) or social and environmental responsibility is an effort made by companies or the business world to contribute to sustainable economic development by paying attention to social responsibility based on a balance of economic, social and environmental values. However, in practice, many CSR programs that have been provided are still not running as expected due to the lack of participation or support from the community in managing so that the program becomes useless because it is not sustainable. This study aims to find out the problems of using PT Pertamina's CSR program in the Klayas Village community. The research method used a qualitative descriptive approach. Problems or problems regarding the termination of the CSR program of PT. Pertamina is caused by the inability of the community to manage and utilize the program. The lack of knowledge and the lack of income obtained from the program make people less interested in the programs provided. So that leaves only a few members who persist in managing it